2009
DOI: 10.1590/s1677-04202009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine improves salt tolerance in vinal (Prosopis ruscifolia Griesbach) seedlings

Abstract: Glycinebetaine (GB) is a very important organic osmolyte that accumulates in a number of diverse groups of plants in response to environmental stress. In some plants, increased resistance to drought, salinity and low temperature has been achieved through exogenous application of GB. In this study, the effect of exogenously applied GB (8 mM) on the ability of vinal (Prosopis ruscifolia G.) plants to withstand NaCl stress was investigated. The dry biomass of vinal showed a decrease under salt stress, but in GBtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 53 publications
(65 reference statements)
2
20
0
Order By: Relevance
“…Salvadora persica (Ramoliya et al 2004), Olea europea (Chartzoulakis et al 2002), and Simmondsia chinesis (Roussos et al 2006). However, growth inhibition in a plant due to salt or alkali stress could occur due to regulation of a multitude of physiological and biochemical processes such as water relations (Munns 2002;Meloni & Martinez 2009;Ahmad et al 2012b), ion transport and accumulation (Hasegawa et al 2000), photosynthesis (Dubey 2005;Ashraf et al 2008), accumulation of osmoprotectants (Ashraf & Foolad 2007;Koyro et al 2012;Katare et al 2012), synthesis of antioxidant enzymatic and nonenzymatic molecules (Mittler 2002;Patade et al 2011;Bano et al 2013;Kaya et al 2013;Rasool et al 2013), synthesis of plant growth regulators (Ashraf et al 2010), mineral nutrient metabolism (Marschner 1995), and many others. One of the most important biochemical responses of plants to abiotic stresses is overproduction of different types of compatible solutes such as proline, glycine betaine, sugars, soluble proteins, amino acids, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Salvadora persica (Ramoliya et al 2004), Olea europea (Chartzoulakis et al 2002), and Simmondsia chinesis (Roussos et al 2006). However, growth inhibition in a plant due to salt or alkali stress could occur due to regulation of a multitude of physiological and biochemical processes such as water relations (Munns 2002;Meloni & Martinez 2009;Ahmad et al 2012b), ion transport and accumulation (Hasegawa et al 2000), photosynthesis (Dubey 2005;Ashraf et al 2008), accumulation of osmoprotectants (Ashraf & Foolad 2007;Koyro et al 2012;Katare et al 2012), synthesis of antioxidant enzymatic and nonenzymatic molecules (Mittler 2002;Patade et al 2011;Bano et al 2013;Kaya et al 2013;Rasool et al 2013), synthesis of plant growth regulators (Ashraf et al 2010), mineral nutrient metabolism (Marschner 1995), and many others. One of the most important biochemical responses of plants to abiotic stresses is overproduction of different types of compatible solutes such as proline, glycine betaine, sugars, soluble proteins, amino acids, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous GB alleviated the inhibitory effect of salt stress, whereas it inhibited the plant vertical growth under non-salinity conditions. It seems that addition of GB alone slightly affects the growth and the protective effect of GB is apparent only under conditions of salt stress (Meloni and Martínez, 2009). Water status is highly sensitive to salinity and therefore is dominant in determining the plant responses to stress (Stepien and Klobus, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that GB alleviated lipid peroxidation and facilitated the maintenance of membrane functions under salinity conditions. This facilitation could be attributed to the GB-induced antioxidant responses that protect the plant from oxidative damage (Hoque et al, 2007;Meloni and Martínez, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their osmoprotective roles, both proline and betaine contribute to scavenging free radicals and buffering cellular redox potential and stabilize many functional units such as the complex II electron transport, membranes and proteins under stressful conditions (McNeil et al, 2001;Molinari et al, 2004). Higher antioxidative enzyme activities in stress conditions either by in vivo proline or betaine synthesis or by exogenous application have also been shown to improve salt stress tolerance (Hoque et al, 2007;Raza et al, 2007;Huang et al, 2009;Ahmad et al, 2010b;Meloni and Martinez, 2010). To our knowledge, there is currently no information available on the possible beneficial effects of exogenous proline or betaine in AsA-GSH cycle in mung bean seedlings grown under salinity conditions.…”
Section: Introductionmentioning
confidence: 99%